PENGARUH PENILAIAN PRESTASI KERJA TERHADAP PROMOSI KARYAWAN PT SAI INDONESIA CABANG YOGYAKARTA - Airin Ratnaningtyas; Utik Bidayati (Jurnal Fokus Manajemen Bisnis, 2011)
The purpose of this study was to identify the influence of employees' performance appraisal (Responsibility, Cooperation, and the Initiative) to the promotion of employees in PT. SAI Indonesia Yogyakarta Branch partially and to identify the influence of employees' performance appraisal (Responsibility, Cooperation, and the Initiative) to the promotion of employees in PT. SAI Indonesia Yogyakarta Branch together.The population in this study were all employees of the non-promotion PT SAI Indonesia Yogyakarta Branch. The sample is selected by using the method of saturated samples, based on the population described above, subsequent samples taken by investigators that were 58 employees. As well as measuring instruments used were variables using Likert scale. This study used multiple linear regression analysis.Based on the test results of t test on the responsibility of the variable not to affect the promotion of employees. Results of t test variable cooperation no effect on the promotion of employees. Later in the third variable that is the initiative contributes to the promotion of employees.